1992
DOI: 10.1017/s0950268800050524
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of enteric adenovirus infection in prospectively monitored Argentine families

Abstract: SUMMARYTo examine the role of enteric adenoviruses (EAV) in an urban area of Buenos Aires (Argentina), we prospectively studied faecal samples from 49 families of newborns. These were monitored weekly for diarrhoea for 2 years.A total of 180 samples from cases of diarrhoea and 766 samples obtained during diarrhoea-free periods were studied by dot-blot hybridization with an EAV-specific DNA probe. EAV were found in 6/180 (33 %) cases of diarrhoea and 6/766 (0-8 %) asymptomatic samples (P < 0015). Incidence of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…The incidence of enteric adenovirus‐associated gastroenteritis diagnosed by PCR was 6.4%, which is similar to that observed in other studies using conventional diagnostic methods for enteric adenoviruses (6‐18). We also performed an EIA screening of the same stool specimens using adenovirus type 2 hexon antibody as the detector.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The incidence of enteric adenovirus‐associated gastroenteritis diagnosed by PCR was 6.4%, which is similar to that observed in other studies using conventional diagnostic methods for enteric adenoviruses (6‐18). We also performed an EIA screening of the same stool specimens using adenovirus type 2 hexon antibody as the detector.…”
Section: Discussionsupporting
confidence: 87%
“…Enteric adenoviruses types 40 and 41 (Ad 40 and Ad 41) are generally regarded as causative agents of acute gastroenteritis in young children (1‐3), whereas other adenoviruses, although frequently detected in stools of both sick and healthy persons (4,5), are not. Studies on enteric adenoviruses in children in hospitals or in those in the community have found the causative role of enteric adenoviruses in acute diarrhea between 0.7% and 14.0% (1,2,5‐18).…”
mentioning
confidence: 99%
“…Other hospital-based series indicate that nosocomially acquired EAd infections form a major proportion of cases (15,31). Rates obtained from outpatient settings or family studies have shown a similar range of 2 to 5.4% for EAd gastroenteritis (17,21). An earlier survey from Melbourne reported that 8.9% of children who presented to a primary care facility and 7.4% of children admitted to hospital with acute diarrhea had EAd identified from fecal specimens (19).…”
Section: Discussionmentioning
confidence: 95%
“…In the United States, the United Kingdom, northern Europe, and Japan, caliciviruses such as the Norwalk and Sapporo viruses are the most common cause of sporadic acute gastrointestinal illness in patients of all age groups except infants and toddlers, in whom rotaviruses predominate. [52][53][54] Adenovirus types 40 and 41 55,56 and astroviruses [57][58][59] have also been implicated. Caliciviruses and astroviruses are more prevalent among outpatients, whereas rotavirus is a common cause of hospitalization.…”
Section: Table 2 Factors That May Contribute To Contagion Of Acute Gmentioning
confidence: 99%